Novel chrono-cultural constraints for the Middle Paleolithic site of Rosh Ein Mor (D15), Israel. (April 2019) - Goder-Goldberger, Mae; Bar-Matthews, Mira
Abstract: The site of Rosh Ein Mor is constantly used as a cultural marker for the presence of "Tabun D" type industries in the Negev. A re-analysis of the lithic assemblage shows that the techno-typological characteristics fit better within the late Middle Paleolithic variability than within the early Middle Paleolithic. Using the powerful tool of U-series for dating calcite crusts on the artifacts a cluster of dates between ~70–35 ka has been obtained. Taking into consideration the central Negev highlands paleoclimate record and the geomorphological setting, this study presents valid data to suggest that Rosh Ein Mor was occupied during MIS 4 and possibly into MIS 3. Highlights: This paper presents new chrono-cultural constrains for Rosh Ein Mor (D15), Israel. A Techno-typological review highlight its similarities with late Middle paleolithic sites. UTh dates from calcite crusts on artifacts result in dates spanning between 70 and 35 ka. The data presented places the D15 assemblages within the late Middle Paleolithic. The term Tabun D type should no longer be used to characterize the D15 assemblage.